Detection of “oncometabolite” 2-hydroxyglutarate by magnetic resonance analysis as a biomarker of IDH1/2 mutations in glioma - Kalinina, Juliya (2012)
Somatic mutations in isocitrate dehydrogenase (IDH)1 and 2 have been identified in a subset of gliomas, rendering these tumors with elevated levels of “oncometabolite,” D-2-hydroxyglutarate (2HG). Herein, we report that 2HG can be precisely detected by magnetic resonance (MR) in human glioma specimens and used as a reliable biomarker to identify this subset of tumors. Specifically, we developed a two-dimensional correlation spectroscopy resonance method to reveal the distinctive cross-peak pattern of 2HG in the complex metabolite nuclear MR spectra of brain tumor tissues. This study demonstrates the feasibility, specificity, and selectivity of using MR detection and quantification of 2HG for the diagnosis and classification of IDH1/2 mutation-positive brain tumors. It further opens up the possibility of developing analogous non-invasive MR-based imaging and spectroscopy studies directly in humans in the neuro-oncology clinic.